Visualizing Global Educational Research Trends in Digital Social-Emotional Learning: A Bibliometric Analysis 2015-2025 - Nafi'a, Muhammad Zidni Ilman; Yunita, Mila; Muntafi, Muhammad Syifaul; Pratama, Krisna Raditya (JURNAL PTI (PENDIDIKAN DAN TEKNOLOGI INFORMASI) FAKULTAS KEGURUAN ILMU PENDIDIKAN UNIVERSITA PUTRA INDONESIA "YPTK" PADANG, 2025)
Digital transformation in education is driving the integration of social-emotional aspects into learning, forming the field of Digital Social Emotional Learning (Digital-SEL). This study aims to map global trends in Digital-SEL research from 2015 to 2025 using bibliometric analysis. Data was obtained from Google Scholar and Scopus via Publish or Perish, curated with Mendeley, and visualized using VOSviewer. Results indicate that “social-emotional learning” is the dominant keyword, with strong associations to school contexts and teaching. Five thematic clusters were identified, reflecting a focus on student emotional well-being, digital technology integration, and innovative pedagogy. Terms like digital storytelling and online learning are gaining attention but have not yet demonstrated strong conceptual depth. This study confirms that Digital-SEL is an evolving interdisciplinary field and encourages cross-disciplinary collaboration to strengthen technology-based pedagogical frameworks.